Conductivity type conversion in p-CdZnTe under pulsed laser irradiation - Tetyorkin, V.V.; Sukach, A.V.; Krolevec, N.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Laser-induced surface modification is investigated in p-Cd₀.₉Zn₀.₁Te under irradiation with nanosecond pulses of YAG:Nd laser by using the power density 5 MW/cm². Conductivity type conversion of the near-surface region with the thickness of several micrometers is observed. The surface-barrier structures were prepared by electrolytic deposition of Au onto the irradiated surface. The spectral dependences of the photovoltaic response has been explained by formation of the graded band gap in the irradiated region. The direct current conductivity has been proved to be determined by the dislocation network.